The analysis of the performance of LQ45 issuers on IDX during the COVID-19 pandemic - Zulfa, Luthfia; Azam, Noer Azam; Bandono, Bayu (International Journal Labs, 2024)
The objective of this study is to examine the factors that have influenced the performance of Indonesian companies listed in the Indonesia Stock Exchange's LQ45 stock index during the COVID-19 pandemic, spanning the period from 2017 to 2022. The study is divided into two main periods: the period preceding the pandemic (2017-2019) and the period following the pandemic (2020-2022). The coefficient of determination (R²) is employed to ascertain the extent to which independent variables, including liquidity, leverage, profitability, activity, managerial ownership, institutional ownership, company size, and company age, can explain variations in the dependent variable, namely company performance. The results demonstrate that leverage has a significant negative impact on company performance, whereas managerial ownership does not affect both groups. Conversely, institutional ownership exerts a positive and significant influence on firm performance. This study offers insights into the factors that can be regulated or monitored to maintain the company's stability and growth. Additionally, it enhances knowledge of firms' ability to survive in challenging economic conditions and provides implications for regulators and investors.